HUMANITIES LECTURER IN E-LEARNING MODE: «SOUL EXCITEMENT» - Alevtina S. Robotova (Высшее образование в России)
The article addresses the personal perception of the distance learning by a Humanities teacher, the solution of the resulting problems: how to create electronic text on Humanities, to save its dialogism; how to overcome alienation with invisible students; how to shape your own style. Special attention is paid to the organization of adequate online communication while studying the problem of spiritual and moral education. The solution of these problems is associated with the «soul excitement» of a teacher. The author argues that the pedagogical reality urgently needs today a phenomenological description in contrast to theoretical studies.